Table of contents; From the Editor's Viewpoint: the New Seriousness: To What Purpose - Charles E Litz; Warren I. Paul (Educational Considerations, 1973)
This content includes the table of contents, a note from the editor, and editorial information for Vol. 1, no. 2, Fall 1973